'All illness is personal to that individual': a qualitative study of patients' perspectives on treatment adherence in bronchiectasis. (20th June 2014) - McCullough, Amanda R.; Tunney, Michael M.; Elborn, J. Stuart; Bradley, Judy M.; Hughes, Carmel M.
Abstract: Background: Adherence to treatment is low in bronchiectasis and is associated with poorer health outcomes. Factors affecting adherence decisions have not been explored in patients with bronchiectasis. Objective: We aimed to explore patients' perspectives on adherence, factors affecting adherence decision making and to develop a conceptual model explaining this decision‐making process in adults with bronchiectasis. Methods: Adults with bronchiectasis participated in one‐to‐one semi‐structured interviews. Interviews were audio‐recorded, transcribed verbatim and analysed independently by two researchers using thematic analysis. Data from core themes were extracted, categorized into factors affecting adherence decision making and used to develop the conceptual model. Results: Participants' beliefs about treatment, the practical aspects of managing treatment, their trust in health‐care professionals and acceptance of disease and treatment were important aspects of treatment adherence. The conceptual model demonstrated that adherence decisions were influenced by participants' individual balance of barriers and motivating factors (treatment‐related, disease‐related, health‐care‐related, personal and social factors). Conclusion: Adherence decision‐making in bronchiectasis is complex, but there is the potential to enhance adherence by understanding patients' specific barriers and motivators to adherence and using this to tailor adherence strategies to individual patients and treatments.